Teaching and learning in information retrieval - Efthimiadis, Efthimis Nikolaos (Information retrieval series, 31, 2011)
With information retrieval a growing field of research, teaching it requires new resources. This book aims to provide theoretical and practical ideas for teaching IR, a topic which has up to now suffered from a lack of literature on its pedagogical aspects